Comparative Histological Subtyping of Immune Cell Infiltrates in MPO-ANCA and PR3-ANCA Glomerulonephritis - Hakroush, Samy; Tampe, Désirée; Ströbel, Philipp; Korsten, Peter; Tampe, Björn (Frontiers in Immunology, 2021)
Background Acute kidney injury (AKI) is a common and severe complication of anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV), potentially leading to chronic kidney disease (CKD), end-stage renal disease (ESRD), or death. Pathogenic ANCAs, in particular proteinase 3 (PR3) and myeloperoxidase (MPO), trigger a deleterious immune response with intrarenal immune cell infiltration resulting in a pauci-immune necrotizing and crescentic glomerulonephritis (GN). However, a systematic analysis of intrarenal immune cell subtypes concerning neutrophils, eosinophils, plasma cells, and mononuclear cell infiltrates (macrophages, lymphocytes) in ANCA GN remains elusive. Therefore, we aimed to compare distinct immune cell infiltrates in association with clinicopathological findings in ANCA GN. Methods A total of 53 kidney biopsies with ANCA GN at the University Medical Center Göttingen were retrospectively analyzed. Histological infiltrates of neutrophils, eosinophils, plasma cells, and mononucleated cells (macrophages, lymphocytes) were quantified as a fraction of the total area of inflammation. Results Neutrophilic infiltrates were associated with glomerular necrosis and severe kidney injury in ANCA GN. Among tubulointerstitial lesions, intrarenal neutrophils correlated with interstitial inflammation, tubulitis, and inflammation in areas of interstitial fibrosis/tubular atrophy (IFTA), representing active inflammatory lesions. Concerning eosinophils, infiltrates were associated with severe kidney injury, interstitial inflammation, and cellular casts independent of glomerular lesions, implicating a distinct role in inflammation and damage in ANCA GN. Plasma cell infiltrates correlated with tubulitis and interstitial fibrosis and were associated with renal replacement therapy during the short-term disease course. Finally, mononuclear cell infiltrates correlated with severe kidney injury and active histopathological lesions (glomerular crescents, interstitial inflammation, tubulitis, inflammation, and tubulitis in areas of IFTA) besides chronic lesions (interstitial fibrosis and tubular atrophy) in ANCA GN. Interestingly, intrarenal subtypes of immune cell infiltrates differed in MPO-ANCA versus PR3-ANCA GN and were associated with distinct glomerular and tubulointerstitial lesions, implicating different pathogenic mechanisms of kidney injury in ANCA subtypes. Conclusion Our observations imply distinct pathomechanisms contributing to inflammation and renal injury in MPO vs. PR3-associated ANCA GN and potentially contribute to new therapeutic targets in specific ANCA subtypes.